Analisis Gaya Bahasa Dalam Novel " Senja, Hujan, Dan Cerita Yang Telah Usai " Karya Boy Candra - Welly Karmelia; Emi Mutiara (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2024)
Figurative speech is inseparable with literary works, particularly to express intrinsic elements in the works. Practically, authors often insert figurative speech to narrate a story. This study is aimed at analyzing figurative speeches in novel Senja, Hujan, dan Cerita Yang Telah Usai, written by Boy Candra. The researcher employed literary study to finish the study which initiated by (i) reading the research object, (ii) collecting the data by marking, identifying, and transcribing. The data were analyzed by using interactive model of analysis. The result showed that the author used 6 types of f igurative speeches to describe both the setting and character, as follows; (1) allegory, (2) (2) alusio, (3) antitesis, (4) asindenton, (5)Klimaks, (6)interupsi. The result of the study strongly suggested that the use of figurative speech is clearly necessary to improve the quality of literary works.